TEACHING PROCEDURE TEXT TO THE THIRD YEAR STUDENT OF SMP MUHAMMADIYAH 1 SRAGEN - ARIYANTI, ARIYANTI (2010)
This research aims at describing teaching procedure text to the third year student SMP Muhammadiyah 1 Sragen. It is conducted to know the objective of teaching writing, and the problems faced by the teacher at SMP Muhammadiyah 1 Sragen. The writer gets the data of this research from event, informant, and document. The techniques of collecting data are the observation and intrview of writing teaching-learning process and the problems faced by the teacher at SMP Muhammadiyah Sragen. The result of the analysis shows that the objectives of teaching writing in SMP Muhammadiyah 1 Sragen are enabling to arrange sentences into procedure text, using the ability of rhetorical into procedure text and to the ability to understanding new words into sentences. The teacher has several problems in teaching, namely; class management, different capability of the students, unstable motivation of students, and lacking of media.